Multifunctional Halls and the Place of Cinema in the European Countryside, 1920-1970 - Thissen, Judith (Cinémas, 2017)
Beginning and ending with the question “what is a cinema?” and with a reconsideration of the notion of cinema’s second birth, this article examines the economic and socio-cultural dynamics of film exhibition and film-going in small-town and rural Western Europe, in particular in the Netherlands, Germany and France. Emphasis is placed on the history of itinerant film exhibition in multifunctional venues in the period after the era of the fairground shows—an important aspect of European film culture which has long been overlooked by cinema historians. Insights from these particular experiences of the cinema can help us to reconceptualize the place of cinema in both rural and urban contexts. A crucial aspect of film-going in multifunctional venues is the fact that it was located in spaces that were used for a wide range of commercial and community activities. The author thus advocates a new cinema historiography that breaks away from the fixation on the medium’s singularity to include its relation with the surrounding socio-cultural contexts in which cinema happened.